2017
DOI: 10.1038/ncomms15292
|View full text |Cite
|
Sign up to set email alerts
|

TRPV1 channels are critical brain inflammation detectors and neuropathic pain biomarkers in mice

Abstract: The capsaicin receptor TRPV1 has been widely characterized in the sensory system as a key component of pain and inflammation. A large amount of evidence shows that TRPV1 is also functional in the brain although its role is still debated. Here we report that TRPV1 is highly expressed in microglial cells rather than neurons of the anterior cingulate cortex and other brain areas. We found that stimulation of microglial TRPV1 controls cortical microglia activation per se and indirectly enhances glutamatergic trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
159
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 197 publications
(183 citation statements)
references
References 75 publications
12
159
0
3
Order By: Relevance
“…This demonstration adds one more line of evidence to the emerging theme of microglia as a modulator of neurotransmission (Cantaut-Belarif et al, 2017;Marrone et al, 2017). Intranasal administration of an NGF variant was recently proven to be highly neuroprotective in an AD mouse model: 53FAD mice chronically treated with the neurotrophin showed a dramatic reduction of the plaque load, with a clear evidence of the involvement of microglial cells in the clearance of Ab (Capsoni et al, 2017).…”
Section: Discussionmentioning
confidence: 70%
See 2 more Smart Citations
“…This demonstration adds one more line of evidence to the emerging theme of microglia as a modulator of neurotransmission (Cantaut-Belarif et al, 2017;Marrone et al, 2017). Intranasal administration of an NGF variant was recently proven to be highly neuroprotective in an AD mouse model: 53FAD mice chronically treated with the neurotrophin showed a dramatic reduction of the plaque load, with a clear evidence of the involvement of microglial cells in the clearance of Ab (Capsoni et al, 2017).…”
Section: Discussionmentioning
confidence: 70%
“…Emerging evidence is showing that stimulation of microglia by activation of glial receptors affects neurotransmission (Marrone et al, ; Riazi et al, ). Therefore, we hypothesized that also NGF may indirectly modulate glutamatergic neurotransmission by acting on microglial cells.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Marrone et al clearly demonstrated that stimulation of microglial TRPV1 controls cortical microglia activation per se and indirectly enhances glutamatergic transmission in neurons by promoting extracellular microglial microvesicles shedding. 50) In this context, in an experimental model of Parkinson's disease, the TRPV1 selective agonist capsaicin inhibits microglia-mediated ROS production, leading to the resultant blockade of the death of dopaminergic neurons. 51) Moreover, TRPV1 partially regulates cytokine production induced by elevated hydrostatic pressure in retinal microglia.…”
Section: Physiological and Pathophysiological Roles Of Trpv Channels mentioning
confidence: 99%
“…Activation of TRPV 1 in nociceptive sensory neurons leads to Ca 2+ influx, resulting in membrane depolarization and release of neuropeptides from primary afferent nerve terminals [98]. More recent studies have found that stimulation of microglial TRPV 1 in rat brain controls cortical microglia activation and indirectly enhances glutamatergic transmission in neurons [99]. The three isoforms of PPARs (α, δ, and γ) are nuclear receptors and ligand activated transcriptional factors that play an essential role in energy metabolism.…”
Section: Receptorsmentioning
confidence: 99%